ASSESS_TTIP: Assessing the claimed benefits of the Transatlantic Trade and Investment Partnership - Werner Raza; Jan Grumiller; Lance Taylor; Bernhard Tröster; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2014)
The current negotiations on a transatlantic Free-Trade Agreement between the US and the EU (TTIP) have raised substantial public interest. Several studies have highlighted the positive economic effects of TTIP. A new ÖFSE report shows that these claims are overstated and neglect crucial adjustment costs and the social costs of regulatory change.
Keywords: 330; Freihandelszone; Makroökonomischer Einfluss; Wohlfahrtsanalyse; Soziale Kosten; EU-Staaten; USA